2019
DOI: 10.1016/j.chom.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

HIV Rebound Is Predominantly Fueled by Genetically Identical Viral Expansions from Diverse Reservoirs

Abstract: Highlights d HIV-1 sequences sampled from different reservoirs were compared to rebound viruses in 11 individuals d Rebound viruses can originate from various cellular and anatomical compartments d Cellular proliferation is an important driver of HIV persistence d Cure strategies should take into account the lack of a prominent HIV rebound origin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
159
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 131 publications
(169 citation statements)
references
References 74 publications
9
159
0
1
Order By: Relevance
“…One potential explanation is that qVOA is limited to the blood compartment and does not take into account rebound coming from other anatomical reservoirs. As shown by De Scheerder et al rebound is heterogeneous and can be fuelled by any infected cell in any anatomical reservoir, making it difficult to have an in vitro proxy [37]. Another potential explanation is the dynamic nature of the viral reservoir, which implicates that sequences between different time points and the observed clones might wax and wane [36,38].…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation is that qVOA is limited to the blood compartment and does not take into account rebound coming from other anatomical reservoirs. As shown by De Scheerder et al rebound is heterogeneous and can be fuelled by any infected cell in any anatomical reservoir, making it difficult to have an in vitro proxy [37]. Another potential explanation is the dynamic nature of the viral reservoir, which implicates that sequences between different time points and the observed clones might wax and wane [36,38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the group of Sarah Palmer indicated that analytical treatment interruption (ATI) activated proviruses with similar sequence between plasma and intestinal lamina propria mononuclear cells (Barton et al, 2016), indicating that intestinal HIV-1 reservoir is contributing to viremia following ATI. A recent study by the group of Linos Vandekerckhove confirmed the heterogeneous source of viral rebound from distinct anatomical reservoirs in HIV-1 individuals undergoing treatment interruption, showing that genetically-identical viral expansions play a significant role in viral rebound (De Scheerder et al, 2019). In a study presented by Oliveira et al (CROI 2019, Poster 327-Characterizing the HIV DNA reservoirs in wholebody tissues in the "Last Gift" cohort), HIV-1 DNA was detected in most body tissues with a nice distribution and compartmentalization of HIV-1 reservoir between tissues from the Last Gift cohort enrolling altruistic, terminally-ill persons living with HIV-1.…”
Section: Hiv-1 Diversity Within the Latent And Reactivated Reservoirsmentioning
confidence: 95%
“…Current combination antiretroviral therapy (cART) can successfully control human immunodeficiency virus type 1 (HIV-1) infection and prevent disease progression to the acquired immunodeficiency syndrome (AIDS). However, a cure is not generally achievable due to the establishment of a latent reservoir of proviral HIV-1 DNA which remains dormant and fuels viral rebound upon treatment interruption [1][2][3][4]. Therefore, better insight into the mechanisms regulating HIV-1 latency is crucial in order to interfere with this latency state and to develop cure strategies.…”
Section: Introductionmentioning
confidence: 99%